Unifying theories of programming and formal engineering methods : International Training School on Software Engineering, Held at ICTAC 2013, Shanghai, China, August 26-30, 2013, Advanced Lectures - Woodcock, Jim; Zhu, Huibiao; Liu, Zhiming (Lecture Notes in Computer Science, 2013)
This book presents 5 tutorial lectures by leading researchers given at the ICTAC 2013 Software Engineering School on Unifying Theories of Programming and Formal Engineering Methods, held in Shanghai, China in August 2013.The lectures are aimed at postgraduate students, researchers, academics, and industrial engineers. They cover topics such as component-based and service-oriented systems, real-time systems, hybrid systems, cyber physical systems, and present techniques such as inductive theorem proving, model checking, correction by construction through refinement and model transformations, synthesis, and computer algebra. Two of the courses are explicitly related to Hoare and He's Unifying Theories of Programming.